ANALISIS TRANSFORMASI PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL DI SDN 193 MANDALAN - Nur Laila; Suardi (STKIP Subang, 2025)
The transformation of learning based on digital technology has become an essential need in the world of education, including at the elementary school level, in line with technological advancements and educational policies that promote the digitalization of learning. This research employs a qualitative approach with a descriptive research design. The research subjects include teachers and fourth-grade students at SDN 193 Mandalan. Data collection was conducted through observation, in-depth interviews, document analysis, and student group discussions. Data analysis involved data reduction, data presentation, and drawing conclusions. The research findings indicate that digital technology-based learning has begun to be implemented through the utilization of digital media such as instructional videos and interactive presentations, which are capable of enhancing student engagement and learning motivation. However, the digital learning transformation has not yet progressed optimally due to limitations in facilities and infrastructure, low digital literacy among some teachers, and the absence of a school culture that supports sustainable digital learning. This research concludes that the transformation of digital technology-based learning in elementary schools requires school policy support, enhancement of teacher competencies, and systematic lesson planning to ensure that digital learning can run effectively and sustainably.